Detection and Quantification of Functional Genes of Cellulose- Degrading, Fermentative, and Sulfate-Reducing Bacteria and Methanogenic Archaea - Pereyra, L. P. (American Society for Microbiology (ASM), 2010)
Cellulose degradation, fermentation, sulfate reduction, and methanogenesis are microbial processes that coexist in a variety of natural and engineered anaerobic environments. Compared to the study of 16S rRNA genes, the study of the genes encoding the enzymes responsible for these phylogenetically diverse functions is advantageous because it provides direct functional information. However, no methods are available for the broad quantification of these genes from uncultured microbes characteristic of complex environments. In this study, consensus degenerate hybrid oligonucleotide primers were designed and validated to amplify both sequenced and unsequenced glycoside hydrolase genes of cellulose-degrading bacteria, hydA genes of fermentative bacteria, dsrA genes of sulfate-reducing bacteria, and mcrA genes of methanogenic archaea. Specificity was verified in silico and by cloning and sequencing of PCR products obtained from an environmental sample characterized by the target functions. The primer pairs were further adapted to quantitative PCR (Q-PCR), and the method was demonstrated on samples obtained from two sulfate-reducing bioreactors treating mine drainage, one lignocellulose based and the other ethanol fed. As expected, the Q-PCR analysis revealed that the lignocellulose-based bioreactor contained higher numbers of cellulose degraders, fermenters, and methanogens, while the ethanol-fed bioreactor was enriched in sulfate reducers. The suite of primers developed represents a significant advance over prior work, which, for the most part, has targeted only pure cultures or has suffered from low specificity. Furthermore, ensuring the suitability of the primers for Q-PCR provided broad quantitative access to genes that drive critical anaerobic catalytic processes.